2011
DOI: 10.1093/cvr/cvr218
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of CD73 promotes atherogenesis in apolipoprotein E-deficient mice

Abstract: Lack of CD73 promotes atherogenesis most likely by de-inhibition of resident macrophages and T cells. Elevated Edn1 and TG levels may have contributed. This establishes CD73-derived adenosine as a direct or indirect regulator of atherogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…This interpretation is supported by the association of increasing serum CD73 activity with the overall burden of atherosclerosis obtained using two different measures of disease severity. Comparably, Buccheiser et al found that CD73 activity and expression in ApoE(−/−) mice increases during the development of atherosclerotic plaques over time [3]. Unfortunately, in the current setting, this interpretation is limited by the fact that CD73 is an ubiquitous enzyme and circulating CD73 activity integrates shedding from various cellular sources and not only from endothelial cells.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This interpretation is supported by the association of increasing serum CD73 activity with the overall burden of atherosclerosis obtained using two different measures of disease severity. Comparably, Buccheiser et al found that CD73 activity and expression in ApoE(−/−) mice increases during the development of atherosclerotic plaques over time [3]. Unfortunately, in the current setting, this interpretation is limited by the fact that CD73 is an ubiquitous enzyme and circulating CD73 activity integrates shedding from various cellular sources and not only from endothelial cells.…”
Section: Discussionmentioning
confidence: 85%
“…Impaired CD73-derived (ecto-5′-nucleotidase) adenosine production has been shown to contribute to the development of atherosclerosis both in mice and men [2][3][4] and also leading to the calcification of lower limb arteries in man [5]. Therefore, we recently explored CD73 activity in blood samples of a wellestablished cohort of patients with symptomatic lower limb atherosclerosis, which is more commonly referred to as peripheral artery disease (PAD) [6].…”
Section: Introductionmentioning
confidence: 99%
“…One such therapeutic target is CD73, an ectoenzyme that catalyzes the generation of adenosine; a potently immunosuppressive host nucleoside. CD73 is expressed on lymphocytes, endothelial and epithelial cells and plays a physiological role in ion transport, maintaining barrier function, endothelial homeostasis and cardioprotection in response to ischemia [6,7] (reviewed in [8]). The focus of this review is the impact of CD73 on suppressing immune responses and its potential as a therapeutic target in cancer.…”
Section: Tumor Immunosuppression and Progression Of Cancermentioning
confidence: 99%
“…It has been shown that ecto-59-nucleotidase/CD73-derived adenosine acts as an endogenous modulator protecting against vascular inflammation and monocyte recruitment, thus limiting the progression of atherosclerosis. Deletion of ecto-59-nucleotidase/CD73 in mice, which leads to a reduction of adenosine, promotes atherogenesis, most likely by de-inhibition of resident macrophages and T cells (Buchheiser et al, 2011), but did not alter angiogenesis (Böring et al, 2013). ET A receptor antagonism restores the myocardial perfusion response to adenosine in experimental hypercholesterolemia (Bonetti et al, 2003).…”
Section: B Atherosclerosis and Coronary Artery Diseasementioning
confidence: 99%